Electroretinographic Assessment of Inner Retinal Signaling in the Isolated and Superfused Murine Retina. (2nd November 2017) - Albanna, Walid; Lueke, Jan Niklas; Sjapic, Volha; Kotliar, Konstantin; Hescheler, Jürgen; Clusmann, Hans; Sjapic, Sergej; Alpdogan, Serdar; Schneider, Toni; Schubert, Gerrit Alexander; Neumaier, Felix
ABSTRACT: Purpose : Longer-lasting electroretinographic recordings of the isolated murine retina were initially achieved by modification of a phosphate-buffered nutrient solution originally developed for the bovine retina. During experiments with a more sensitive mouse retina, apparent model-specific limitations were addressed and improvements were analyzed for their contribution to an optimized full electroretinogram (ERG). Material and methods : Retinas were isolated from dark-adapted mice, transferred to a recording chamber and superfused with different solutions. Scotopic and photopic ERGs were recorded with white flashes every 3 minutes. The phosphate buffer (Sickel-medium) originally used was replaced by a carbonate-based system (Ames-medium), the pH of which was adjusted to 7.7–7.8. Moreover, addition of 0.1 mM BaCl2 was investigated to reduce b-wave contamination by the slow PIII component typically present in the murine ERG. Results : B-wave amplitudes were increased by the pH-shift (pH 7.4 to pH 7.7) from 22.9 ± 1.9 µV to 37.5 ± 2.5 µV. Improved b-wave responses were also achieved by adding small amounts of Ba 2+ (100 µM), which selectively suppressed slow PIII components, thereby unmasking more of the true b-wave amplitude (100.0% with vs. 22.2 ± 10.7% without Ba 2+ ). Ames medium lacking amino acids and vitamins was unable to maintain retinal signaling, as evident in a reversible decrease of the b-wave to 31.8 ± 3.9% of its amplitude in complete Ames medium. Conclusions : Our findings provide optimized conditions for ex vivo ERGs from the murine retina and suggest that careful application of Ba 2+ supports reliable isolation of b-wave responses in mice. Under our recording conditions, murine retinas show reproducible ERGs for up to six hours.